Output gap in the Czech economy4DDSGE approach - Jakub Bechný (Review of Economic Perspectives, 2019)
This paper presents three measures of the output gap estimated by a dynamic stochastic general equilibrium model of the Czech economy. We argue that the most plausible description of the business cycle provides the output gap defined as a deviation from a flexible price level of output, which is generated solely by permanent growth shocks. Our model shows that 2006-2008 overheating of the economy and the following 2008-2009 slump can be largely attributed to development in a world economy and export and import sectors, while the 2012-2013 recession was caused mainly by a combination of adverse domestic demand and cost shocks.
Keywords: C32; E32; E47; 330; DSGE model; labour market; output gap; small open economy